The association between cognitive performance and speech-in-noise perception for adult listeners: a systematic literature review and meta‐analysis - Dryden, Adam; Allen, Harriet A.; Henshaw, Helen; Heinrich, Antje (SAGE, 2017)
Published studies assessing the association between cognitive performance and speech-in-noise perception examine different aspects of each, test different listeners, and often report quite variable associations. By examining the published evidence base using a systematic approach, we aim to identify robust patterns across studies and highlight any remaining gaps in knowledge. We limit our assessment to adult non-hearing aid users with audiometric profiles ranging from normal hearing to moderate hearing loss. A total of 253 articles were independently assessed by two researchers, with 25 meeting the criteria for inclusion. Included articles assessed cognitive measures of attention, memory, executive function, IQ and processing speed. Speech-in-noise measures varied by target (phonemes/syllables, words, sentences) and masker type (unmodulated noise, modulated noise, multi (n>2) talker babble, and n<2 talker babble). The overall association between cognitive performance and speech-in-noise perception was r=0.31. For component cognitive domains, the association with (pooled) speech-in-noise perception were; processing speed (r=0.39), inhibitory control (r=0.34), working memory (r=0.28), episodic memory (r=0.26) and crystalized IQ (r=0.18). Similar associations were shown for the different speech target and masker types. This review suggests a general association of r≈0.3 between cognitive performance and speech perception, although some variability in association appeared to exist depending on cognitive domain and speech-in-noise target or masker assessed. Where assessed, degree of unaided hearing loss did not play a major moderating role. We identify a number of cognitive performance and speech-in-noise perception combinations that have not been tested, and whose future investigation would enable further finer-grained analyses of these relationships.